Peran Aliansi Masyarakat Adat Nusantara (AMAN) dalam Konflik Lahan Pandumaan-Sipituhuta dengan PT. Toba Pulp Lestari - Elkanalisa Togatorop; Muliono Muliono; Galank Pratama (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2026)
The land conflict between the Pandumaan-Sipituhuta indigenous community and PT Toba Pulp Lestari is a form of agrarian conflict involving claims to control customary territory and corporate interests. This study aims to analyze the role of the Indigenous Peoples Alliance of the Archipelago (AMAN) in this conflict. The approach used was qualitative with data collection techniques through in-depth interviews and documentation studies. The results of the study indicate that AMAN plays a significant role in various aspects, such as legal assistance, mass mobilization, community organizing, legal education, and village deliberations. In addition, AMAN also builds networks with various parties to strengthen the bargaining position of indigenous communities. Through these roles, AMAN has succeeded in increasing the bargaining power of the Pandumaan-Sipituhuta indigenous community in facing the conflict with PT Toba Pulp Lestari. This study confirms that advocacy organizations such as AMAN have a crucial role in fighting for the rights of indigenous communities in land disputes, as well as being agents of change in resolving agrarian conflicts.